The Effectiveness of Coastal Environment-Based PBL in Improving Students’ Ecological Literacy and Learning Outcomes in Biodiversity Ecology - Nyoman Sriastuti; Abdul Haris Odja; Masrid Pikoli; Frida Maryati Yusuf; Ramli Ali (Journal of Educational Sciences, 2026)
This study examined the effectiveness of coastal environment-based Problem-Based Learning (PBL) in improving students’ ecological literacy and learning outcomes in biodiversity ecology. The research was motivated by the need to make ecology and biodiversity learning more contextual, meaningful, and connected to students’ surrounding environmental realities. A quantitative pre-experimental method with a one-group pretest-posttest design was employed. The participants were 30 seventh-grade students at SMP Negeri 2 Bokan Kepulauan, Banggai Laut Regency, selected through saturated sampling. Data were collected using a 25-item multiple-choice learning outcomes test, an ecological literacy questionnaire, and a student activity observation sheet. The data were analyzed using the Shapiro-Wilk normality test, Wilcoxon Signed Rank Test, normalized gain, and descriptive percentage analysis. The results showed a significant improvement in students’ learning outcomes and ecological literacy after the implementation of coastal environment-based PBL. The N-gain score for learning outcomes reached 0.713, while ecological literacy reached 0.74, both categorized as high. Student activity also remained consistently high during the learning sessions. These findings indicate that coastal environment-based PBL is effective in enhancing students’ conceptual understanding, ecological awareness, and active participation in biodiversity ecology learning.